IDENTIFICATION OF THE PHILOSOPHY, TRADITIONS AND THE CONCEPT OF ISLAMIC EDUCATION AND ITS IMPLEMENTATION IN THE DESIGN OF ARCHITECTURE - Izzuddin, Achmad; Poerwoningsih, Dina (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Education in Islam plays an important role in the progress of a nation. Through basic education the transformation of philosophy and tradition, Islam developed into a concept in life. The concept of education in Indonesia is supposed to accommodate the values of Islam that became the basis of the life of most of the Indonesian nation. The main tradition of education in Islam Al-Qur'an and Al-Hadith emphasizes on akhlaqul Karimah which originated from informal education from mosque activities or surau and in its development became a pesantren. In its development in line with the advancement of the era and the demands of the government curriculum, pesantren developed into a formal educational institution in the form of madrassas that adhered to the philosophy, traditions and concepts of Islamic education. Implementation of these developments is the demand of educational activities based on general education and religion that have different characteristics to the needs of specific facilities architecturally. For example is the need for space for teaching the science of religion more than just a mosque. This paper aims to explore the philosophy, traditions and concepts of Islamic education through the study of a number of references that are expected to contribute to the sustainability of Islamic values in education in Indonesia. This paper also tries to link it to several examples of the implementation of Islamic values in spatial and architectural concepts.